In Arabidopsis thaliana, RNA-Induced Silencing Complex-Loading of MicroRNAs Plays a Minor Regulatory Role During Photomorphogenesis Except for miR163 - Lakatos, Lóránt; Groma, Gergely; Silhavy, Daniel; Nagy, Ferenc (Frontiers in Plant Science, 2022)
The shift of dark-grown seedlings to the light leads to substantial reprogramming of gene expression, which results in dramatic developmental changes (referred to as de-etiolation or photomorphogenesis). MicroRNAs (miRNAs) regulate most steps of plant development, thus miRNAs might play important role in transcriptional reprogramming during de-etiolation. Indeed, miRNA biogenesis mutants show aberrant de-etiolation. Previous works showed that the total miRNA expression pattern (total miRNAome) is only moderately altered during photomorphogenesis. However, a recent study has shown that plant miRNAs are present in two pools, biologically active miRNAs loaded to RISC (RNA-induced silencing complex-loaded) form while inactive miRNAs accumulate in duplex form upon organ formation. To test if RISC-loading efficiency is changed during photomorphogenesis. we compared the total miRNAome and the RISC-loaded miRNAome of dark-grown and de-etiolated Arabidopsis thaliana seedlings. miRNA sequencing has revealed that although regulated RISC-loading is involved in the control of active miRNAome formation during de-etiolation, this effect is moderate. The total miRNAomes and the RISC-loaded miRNAomes of dark-grown and de-etiolated plants are similar indicating that most miRNAs are loaded onto RISC with similar efficiency in dark and light. Few miRNAs were loaded onto RISC with different efficiency and one miRNA, miR163, was RISC-loaded much more effectively in light than in dark. Thus, our results suggest that although RISC-loading contributes significantly to the control of the formation of organ-specific active miRNA pools, it plays a limited role in the regulation of active miRNA pool formation during de-etiolation. Regulated RISC-loading strongly modifies the expression of miRNA163, could play a role in the fine-tuning of a few other miRNAs, and do not modify the expression of most miRNAs.